Thromboembolic complications in oncology - Stanisławiak, Joanna; Markowska, Janina (Menopause Review/Przegląd Menopauzalny, 2010)
Thrombosis is a frequent complication of cancer. Cancer is associated with a 4-fold greater risk of thrombosis. Armand Trousseau was the first man to describe the connection between thrombosis and cancer. Rudolf Virchow described “Virchov’s Triade”, which leads to three broad categories of factors that are thought to contribute to thrombosis. The risk factors of thrombosis differ across the natural history of the cancer, treatment of the cancer and cancer patient. The symptoms of thrombosis are the same in cancer and non-cancer patients. Hospitalized patients with cancer should be considered as candidates for VTE prophylaxis with anticoagulants. All patients undergoing surgical intervention for malignant disease should receive thromboprophylaxis for 4-6 weeks after the surgical procedure. Routine prophylaxis with an antithrombic agent is not recommended for ambulatory patients with cancer unless there are patients receiving thalidomide or lenalidomide with chemotherapy or dexamethazone. The mechanical methods of thromboprophylaxis should be used with pharmacological methods. Low-molecular weight heparin is the preferred approach for treatment of thrombosis. Vitamin K antagonists are acceptable with targeted INR of 2 to 3. The insertion of a vena cava filter is indicated for patients with contraindications to anticoagulant therapy and those with recurrent VTE.